Agricultural diversity and child stunting in Nepal - Shively, Gerald E.; Sununtnasuk, Celeste (Informa UK Limited, 2015)
This article investigates empirical connections between agriculture and child nutrition in Nepal. We augment the standard approach to explaining child nutrition outcomes by including information about household level agricultural production characteristics, including indicators of agricultural diversity. Data from the 2010/2011 Nepal Living Standards Survey (NLSS) are used in a series of regression models to explain stunting outcomes and variation in height-for-age Z-scores among 1,769 children 0–59 months of age. Results highlight the relative importance of overall agricultural yields, specific crop groups, and the consumption of own-production as factors correlated with long-term nutrition among children of different age groups. We find a small positive association between the degree of commercial market-orientation of households and child HAZ, but only among children under 24 months of age.